PENGARUH KOSAKATA DAN STRUKTUR BAHASA ARAB TERHADAP CARA BERPIKIR DAN BUDAYA BELAJAR PERSPEKTIF SAPIR-WHORF - Jayadi, M. Irwan; Thayyibah, Uyun; Royani, Ahmad; Fudhaili, Achmad (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The relationship between language, mind and culture is inherent and mutually influential. One of the familier theories regarding the relationship between the three is the Sapir -Whorf theory. The purpose of this writing is to find out the influence of Arabic vocabulary and structure on the way of thinking and learning culture of Maskanul Huffadz Lil Lughoh students based on the Sapir-Whorf perspective. This type of research is descriptive qualitative with data collection techniques, using observation, interviews and documentation. The results of the analysis of the data found that mastery of Arabic vocabulary and structure on the way of thinking and learning culture of Maskanul al-Huffadz Li al-Lughoh students affects the way of thinking about time and sequence of events. This is evident from the results of the analysis of the answers of the students who feel that after learning Arabic they are more able to think logically and systematically when they want to plan activities. They are more accustomed to distinguishing clearly between actions that have been completed, are in progress, or will be carried out. The students also become more analytical and detailed in processing information because they have to understand complex grammar and rich vocabulary.